ANALISIS BUKTI DIGITAL PADA APLIKASI DISCORD DESKTOP DENGAN MENGGUNAKAN FRAMEWORK DFRWS - Wibowo, Mukti; Firmansyah, Mohammad Raffli; Efendi, Rezar Surya (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
A Currently, various communication platforms are available, and one of them is Discord. Discord is utilized by users to interact and share various types of content. However, Discord is often implicated in the distribution of inappropriate content that goes against Discord regulations. This can lead to cybercrime cases such as Child Sexual Abuse Material (CSAM). The main challenge faced is the recovery of digitally deleted data through these communication platforms. The objective of this research is to analyze digital evidence in the form of deleted text messages, images, and documents in the chat rooms of the desktop-based Discord application. The research method employed is the Live Forensic Technique, applying the DFRWS (Digital Forensics Research Workshop) method. The digital forensic analysis process is conducted using the digital forensic tool Magnet Axiom. The research results indicate that the accuracy of digital evidence analysis using Magnet Axiom reaches 94.11%. A total of 16 digital evidence items were successfully recovered out of the total 17 items available